Effects of melatonin implants on reproduction and growth of turbot broodstock - Alvariño, J.M.R.; Rebollar, P.G.; Olmedo-Herrero, M. (Mercedes); Álvarez-Blázquez, B. (Blanca); Ubilla, E.; Peleteiro-Alonso, J.B. (José Benito) (Centro Oceanográfico de Vigo, 2023)
The effect of 18 mg. melatonin (MLT) implants on thereproductive performance of turbot (Scophthalmus maximusL.) broodstock was determined in 20 females and 12 males. Implantedanimals showed supra-physiological plasma MLT concentrations during threemonthsafter implantation, being at that time about one hundred times higher thandiurnal MLT concentrations. Direct effects of MLT implants were observed ongonadal maturation of turbot females three months after implantation (P <0.01), although the faster ovarian response to increasing photoperiod was notconsistent and no differences were detected at the final reproductiveperformance. MLT implants had a positive effect on turbot male reproductivefeatures, since gonadal recrudescence started 45 days earlier (P < 0.05)showing a trend towards higher spermatozoa concentration. Further research isadvisable to ascertain the MLT dose required for and time of implantation inturbot broodstock. 0,9120